A Computational Presentation Of Bioelectromagnetic Applications Using Numerical Method Approaches - Ismail, Mohd Muzafar; Janudin, Nur Hazwani; Zakaria, Zahriladha; Othman, Mohd Azlishah (Academy Publisher, 2014)
-